Odpowiedzi

2010-03-25T09:51:27+01:00
A) W(x)= x³+7x²-x-7=x²(x+7)-(x+7)=(x+7)(x²-1)=(x+7)(x-1)(x+1)
b) W(x)=2x³+x²-8x-4=x²(2x-1)-4(2x+1)=(2x+1(x²-4)=(2x+1(x-2)(x+2)

Pozdrawiam

Hans
1 5 1
2010-03-25T09:51:30+01:00
A) W(x)= x³+7x²-x-7 = x²(x+7)-(x+7) = (x+7)(x²-1) = (x+7)(x+1)(x-1)
b) W(x)=2x³+x²-8x-4 = x²(2x+1)-4(2x+1) = (2x+1)(x²-4)(2x+1)(x+2)(x-2)
2010-03-25T09:52:33+01:00
A) W(x)= x³+7x²-x-7 = x²(x+7)-(x+7) = (x+7)(x²-1) = (x+7)(x-1)(x+1)

b) W(x)=2x³+x²-8x-4 = x²(2x+1) - 4(2x+1) = (2x+1)(x²-4) = (2x+1)(x-2)(x+2)